Combined Chemotherapy Regimen of Carboplatin and Paclitaxel as Adjuvant Treatment for Papillary Serous and Clear Cell Endometrial Cancer. Issue 4 (1st April 2009) - Shechter-Maor, Gil; Bruchim, Ilan; Ben-Harim, Zipi; Altaras, Marco; Fishman, Ami
Abstract : Objective: Uterine papillary serous carcinoma (UPSC) and uterine clear cell carcinoma (UCCC) are highly aggressive variants of endometrial cancer. The optimal adjuvant regimen for these uterine malignant types has not yet been defined. The objective of this study was to evaluate the efficacy and toxicity of a combined chemotherapy regimen of carboplatin and paclitaxel as adjuvant treatment for patients with UPSC and UCCC variants. Methods: A retrospective analysis of results of adjuvant chemotherapy that was based on 6 cycles of carboplatin (area under the curve, 5-6) and paclitaxel (175 mg/m 2 ) q3 weeks. Results: Twenty-one patients were eligible for analysis. All patients in this group underwent surgery before chemotherapy, with reported optimal debulking in 90% (n = 19). Fourteen patients (66%) had advanced stage (International Federation of Gynecology and Obstetrics stages III-IV) at the time of diagnosis. Five patients (24%) were treated with pelvic radiotherapy after the chemotherapy regimen. Clinical no-evidence-of-disease status was recorded in 19 patients (90%) at the end of the planned chemotherapy schedule. With a median follow-up of 25 months (8-61 months), 11 patients (58%) had recurrence and all have died of disease. Median progression-free interval was 13 months with a median survival of 27 months. Grade 3 toxicity was recorded in 7 patients (33%). Neutropenia developed in 3 patients (14%), neuropathy in 3 (14%), anaphylaxis in 1 (4.6%), and anemia in 1 (4.6%). Dose reduction was needed in 6 patients (29%), treatment delay in 6 (29%), and treatment cessation in 2 patients (10%). Conclusions: The regimen of carboplatin and paclitaxel is active in patients with UPSC and UCCC with an acceptable toxicity profile.